Control of Polymorphism and Particle Size of Hexanitrohexaazaisowurtzitane in Drowning‐Out Crystallization. Issue 7 (9th June 2017) - Lim, Chaeho; Kim, Hyoun-Soo; Kim, Kwang-Joo
Abstract: Polymorphism and the crystal size of 2, 4, 6, 8, 10‐hexanitro‐2, 4, 6, 8, 10, 12‐hexaazaisowurtzitane (HNIW) were simultaneously controlled in drowning‐out crystallization. The effect of antisolvent to solvent ratio on solubility and polymorphism was studied. Polymorph transformation, interfacial tension, maximum supersaturation, and scaling up of crystallization were investigated. To crystallize the small ε form of HNIW, the supersaturation level was studied by using the solvents isopropanol and acetone. The polymorphic β and ε forms were selected by controlling the supersaturation and mass fraction of the solvent mixture. By controlling the concentration, temperature, and solvent/antisolvent ratio, a micron‐sized ε form was recrystallized. In this study, the optimal conditions to prepare 4–60 μm sized ε form were established on a laboratory scale. Based on laboratory experiments, a commercial‐scale process was performed successfully. Abstract : Drowning‐out crystallization allows effective control of polymorphism and particle sizes. 2, 4, 6, 8, 10‐Hexanitro‐2, 4, 6, 8, 10, 12‐hexaazaisowurtzitane is used as a model compound to determine laboratory‐scale conditions of crystallization for scaling up. The polymorphic β and ε forms were selected by controlling supersaturation and the ratio of components in the solvent mixture.